2019
DOI: 10.1371/journal.pone.0226552
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of therapeutic drug monitoring for imatinib administration in chronic myeloid leukemia

Abstract: BackgroundImatinib mesylate (IM) is a first-line treatment option for patients with chronic myeloid leukemia (CML). Patients who fail or are intolerant to IM therapy are treated with more expensive second and third-generation tyrosine kinase inhibitors. Patients show wide variation in trough concentrations in response to standard dosing. Thus, many patients receive subtherapeutic or supratherapeutic doses. Therapeutic drug monitoring (TDM) may improve dose management that, in turn, may reduce costs and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…This study supports that using therapeutic drug monitoring (TDM) is highly useful in patients with CML treated with IM for adjustment of the dose as suggested by Kim et al. 24 . The current study showed a statistically significantly higher trough IM (1361 ng/ml) among good responders (N=25) compared to lower levels in bad responders (N=25) (1019 ng/ml) ( P=0.007) .…”
Section: Discussionsupporting
confidence: 89%
“…This study supports that using therapeutic drug monitoring (TDM) is highly useful in patients with CML treated with IM for adjustment of the dose as suggested by Kim et al. 24 . The current study showed a statistically significantly higher trough IM (1361 ng/ml) among good responders (N=25) compared to lower levels in bad responders (N=25) (1019 ng/ml) ( P=0.007) .…”
Section: Discussionsupporting
confidence: 89%
“…7 Therapeutic drug monitoring can reduce drug exposure variability and has been shown to be useful in predicting the efficacy of imatinib for chronic myeloid leukemia, 25 but with a modest budget impact. 26 In conclusion, lapatinib administration before breakfast can minimize the effects of food on lapatinib concentration and reduce the incidence of diarrhea and a rash compared with at bedtime dosing. This approach is easy to apply with no added cost or inconvenience to patients, and has the potential to permit dose escalation.…”
Section: Discussionmentioning
confidence: 91%
“…In breast cancer, however, EGFR is not the principal therapeutic target and is not highly co‐expressed with HER2 7 . Therapeutic drug monitoring can reduce drug exposure variability and has been shown to be useful in predicting the efficacy of imatinib for chronic myeloid leukemia, 25 but with a modest budget impact 26 …”
Section: Discussionmentioning
confidence: 99%
“…Second, at first glance, performing TDM in routine care seems expensive. However, considering the direct and indirect costs of treating patients at suboptimal doses, e.g., the costs resulting from treatment progression in underdosed patients and the costs of treating toxicity in overdosed patients, TDM has already been found to be cost-effective for two targeted oral anticancer drugs (tamoxifen [ 44 ] and imatinib [ 44 , 45 ]). Third, ‘traditional’ TDM requires patients to come to their treatment center for venous blood sample collection.…”
Section: Discussionmentioning
confidence: 99%